2015
DOI: 10.1038/ncomms7588
|View full text |Cite
|
Sign up to set email alerts
|

Trained immunity in newborn infants of HBV-infected mothers

Abstract: The newborn immune system is characterized by an impaired Th1-associated immune response. Hepatitis B virus (HBV) transmitted from infected mothers to newborns is thought to exploit the newborns’ immune system immaturity by inducing a state of immune tolerance that facilitates HBV persistence. Contrary to this hypothesis, we demonstrate here that HBV exposure in utero triggers a state of trained immunity, characterized by innate immune cell maturation and Th1 development, which in turn enhances the ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 52 publications
(61 reference statements)
5
119
1
1
Order By: Relevance
“…Based on our results, it is tempting to speculate that insufficient DC activation due to low sCD14 levels may be one of the factors contributing to inadequate HBV-specific immunity in HBV-infected newborns. In a seemingly paradoxical observation, Hong and colleagues recently showed that monocytes of HBVexposed newborns had an enhanced activation state compared to those from unexposed neonates (40). Monocytes, however, in contrast to the BDCA1 ϩ DC that we studied here, are not able to induce activation of naive virus-specific T cells and express membrane CD14 and thus do not depend on sCD14 for their activation.…”
Section: Discussioncontrasting
confidence: 38%
“…Based on our results, it is tempting to speculate that insufficient DC activation due to low sCD14 levels may be one of the factors contributing to inadequate HBV-specific immunity in HBV-infected newborns. In a seemingly paradoxical observation, Hong and colleagues recently showed that monocytes of HBVexposed newborns had an enhanced activation state compared to those from unexposed neonates (40). Monocytes, however, in contrast to the BDCA1 ϩ DC that we studied here, are not able to induce activation of naive virus-specific T cells and express membrane CD14 and thus do not depend on sCD14 for their activation.…”
Section: Discussioncontrasting
confidence: 38%
“…The identification of these nonspecific (or heterologous) effects suggests that these vaccines induce trained immunity that protects against unrelated pathogens. This hypothesis was proposed in proof-of-principle trials with BCG vaccine in healthy adult volunteers (37), and thereafter validated in clinical trials in newborn children vaccinated with BCG (38) or exposed in utero to hepatitis B vaccine (39). Secondly, certain infections such as malaria can also induce a state of hyper-responsiveness that is functionally equivalent to the induction of trained immunity (40, 41).…”
Section: Innate Immune Memory In Vertebratesmentioning
confidence: 99%
“…The clinical course of acute HBV infection with a substantial rise of liver enzymes and bilirubin, the need for the elimination of covalently closed circular DNA, as well as recent findings in cell culture models, however, also supports the contribution of cytolytic effector mechanisms such as perforin and granzyme secretion and induction of the apoptotic Fas/FasL pathway [5, 15,16] . Interestingly, the mechanism of viral persistence in the vast majority of HBV-infected newborns and children remains unclear; T-cells in these young patients are not generally compromised or tolerogenic [17,18] . In HCV infection, findings in patients, chimpanzees as well as a cell culture model indicate that non-cytolytic effector functions have a dominant role [8,10,11,19] .…”
Section: Successful Hbv-and Hcv-specific Cd8+ T-cell Responsementioning
confidence: 99%